Performance of Joint Relay and Antenna Selection in the Full-Duplex Amplify-and-Forward Relay Networks [2] - Toka, Mesut; Kucur, Oğuz; Tezekici, Bekir Sami (IEEE, 2015)
In this work, joint relay and antenna selection (JRAS) problem in Full-Duplex (FD) Amplify-and-Forward (AF) relaying network is examined. A dual-hop relay system with one source, one destination and N FD AF relays is considered. Each FD relay is equipped with N,. antennas for receiving and N, antennas for transmitting. In this FD relay system, joint selection strategy involves choosing the best single relay and the best single receive/transmit antenna at the source-to-relay/relay-to-destination links. The system model is developped and the outage probability (OP) and the bit error rate (BER) of the system for different numbers of relay and antenna cases are examined in Rayleigh fading channel via Monte Carlo simulations.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Dual-hop networks; Full-duplex relaying; Amplify-and-forward; Relay selection; Antenna selection